Peer victimization and social anxiety in adolescence: a comparison between migrant and native students in Italy - Di Tata, Daniele; Bianchi, Dora; Laghi, Fiorenzo (Frontiers in Psychology, 2024)
The first aim of this study is to investigate the relationship between bullying victimization and social anxiety in native and migrant adolescents in Italy. Specifically, it was hypothesized that migrant adolescents (in comparison with natives) experience more frequent episodes of bullying victimization, which in turn, may be a risk factor for the development of social anxiety symptoms. The second aim of the study is to explore the relationships from reflected minority categorization to perceived ethnic discrimination at school and social anxiety symptoms, in the subgroup of migrant students. Results showed that the migrant (vs. native) status was predictive of higher scores in social anxiety dimensions (Fear of Negative Evaluation, Social Avoidance and Distress in New Situations, and General Social Avoidance Distress), via the mediating effect of increased peer victimization. Moreover, in the subgroup of migrant participants, an indirect effect of reflected minority categorization on social anxiety was observed, mediated by perceived ethnic discrimination at school. These findings may contribute to the understanding of health inequalities among migrant and native people in the Italian context. Limitations and practical implications of the study were discussed.